(untitled) (Asian Journal of Medical Research and Health Sciences, 2026)
Background: It is well known that breastfeeding is an important influence on optimal physical, cognitive and emotional development in early childhood. Breast milk contains all the nutrients needed for brain maturation, long-chain polyunsaturated fatty acids, immunological components, and bioactive substances which are beneficial to brain function. Worldwide, it is believed that breastfeeding is linked to an increased intelligence quotient (IQ), however, this has not been sufficiently studied in many low and middle income countries. It is crucial to grasp this linkage in order to design public health policies, parent counseling, and early childhood development interventions. This study was designed to examine the association between breastfeeding and IQ of children. Study design: Comparative cross-sectional study Place and Duration of Study: This study was conducted at Hamdard University of Medicine and Dentistry Karachi from April 2025 to April 2026 Methodology: The study employed a sample of 88 children who had been recruited using non‐probability convenience sampling technique on the basis of predetermined inclusion and exclusion criteria. Ethical Approval and informed consent was taken before data collection. Infants were classified as exclusively breastfed and formula fed. IQ was measured on the Wechsler Intelligence Scale for Children (WISC) which was administered by trained assessors under standardised conditions. Descriptive and inferential statistics were used in analyzing the data. Associations between feeding type, breastfeeding duration and the IQ categories were tested using the chi-square test. A p‑value <0.05 was considered statistically significant. Results: The overall mean WISC IQ score among the 88 children was 108 ± 11. Infants who were breast fed had better cognitive function than those who were formula fed. The mean IQ score of exclusively or predominantly breastfed children was 114 ± 12, whereas children who were primarily formula‑fed had a mean IQ score of 101 ± 13. This difference was statistically significant (p = 0.002). A significant association was found also between cognitive outcomes and duration of breastfeeding. Females breastfed for over 12 months had the highest mean IQ scores, followed by those breastfed for 6-12 months, and comparatively lower scores with those breastfed for less than 6 months. Breastfeeding for more than six months was correlated with IQ (p = 0.03). This indicates a dose‐response relationship, as the longer the duration of breastfeeding, the better the cognitive performance. Conclusion: The study shows that there is a positive relationship between breastfeeding and IQ among children. Furthermore, longer breastfeeding seems to provide other cognitive advantages, which suggests both breastfeeding and breastfeeding duration are important factors in neurodevelopment. The results reaffirm the need to continue to champion breastfeeding as an important public health intervention for optimal cognitive development in early childhood.